Mechanical performance and deformation mechanisms at cryogenic temperatures of 316L stainless steel processed by laser powder bed fusion: In situ neutron diffraction. (September 2022) - Tang, Lei; Magdysyuk, Oxana V.; Jiang, Fuqing; Wang, Yiqiang; Evans, Alexander; Kabra, Saurabh; Cai, Biao
Abstract: Manufacturing austenitic stainless steels (ASSs) using additive manufacturing is of great interest for cryogenic applications. Here, the mechanical and microstructural responses of a 316L ASS built by laser powder bed fusion were revealed by performing in situ neutron diffraction tensile tests at the low-temperature range (from 373 to 10 K). The stacking fault energy almost linearly decreased from 29.2 ± 3.1 mJm −2 at 373 K to 7.5 ± 1.7 mJm −2 at 10 K, with a slope of 0.06 mJm −2 K −1, leading to the transition of the dominant deformation mechanism from strain-induced twinning to martensite formation. As a result, excellent combinations of strength and ductility were achieved at the low-temperature range. Graphical abstract: Image, graphical abstract